ANALISIS PARTISIPASI MURID SMA DALAM PEMBELAJARAN DARING: STUDI PADA MURID KELAS IPS XI SMAS AL-IZHAR JAKARTA - Neni Nuraini; Supriyanto Supriyanto (Jurnal Analisis Pendidikan Sosial, 2023)
The sudden change in the learning process during the pandemic Covid-19 has led to the decreasing level of students’ participation in online schooling process. The research aims to identify how much students take part in classroom activities at SMAS Al-Izhar Jakarta Year 11 Social Class. The research was conducted to 23 sample students who belong to year 11 majoring in social class at SMAS Al-Jakarta. The sample students were chosen by using purpose sampling technique. The research applied descriptive method with qualitative approach. The research was conducted on 19 February until 5 March 2021 by distributing a questionnaire through Google Form format. The data resulted in that the students’ participation in year 11 social class at SMAS Al-Izhar Jakarta is classified good (adequate) in terms of oral, auditory and written classroom activities.